The Roles of Four Novel P450 Genes in Pesticides Resistance in Apis cerana cerana Fabricius: Expression Levels and Detoxification Efficiency - Zhang, Weixing; Yao, Yufeng; Wang, Hongfang; Liu, Zhenguo; Ma, Lanting; Wang, Ying; Xu, Baohua (Frontiers in Genetics, 2019)
Abstract: Cytochrome P450 monooxygenases (P450s) are widely distributed multifunctional enzymes that play crucial roles in insecticide detoxification or activation. In this study, to ascertain the molecular mechanisms of P450s in the detoxification of Chinese honeybees, Apis cerana cerana Fabricius (A. c. cerana), we isolated and characterized four new P450 genes (Acc301A1, Acc303A1, Acc306A1 and Acc315A1). The open reading frames of the four genes are 1263 to 1608 bp in length and encode four predicted polypeptides of 499 to 517 amino acids in length. Real-time quantitative PCR (RT-qPCR) results showed that expression of all four genes was observed in all developmental stages. Additionally, Western blot assays further indicated the real-time quantitative PCR results that showed that the four genes were induced by pesticide (thiamethoxam, deltamethrin, dichlorovos and paraquat) treatments. Furthermore, we also used dsRNA-mediated RNA interference to investigate the functions of Acc301A1, Acc303A1 and Acc306A1 in the antioxidant defense of honeybees. RNA interference targeting Acc301A1, Acc303A1, and Acc306A1 significantly increased the mortality rate of A. c. cerana upon pesticide treatment. These results provide important evidence about the role of the four P450 genes involved in detoxification.